A Rare Etiology of Abnormally Large Gastric Folds: Menetrier's Disease. (31st December 2019) - Kamal, Muhammad Umar; Tariq, Hassan; Mehak, Vaniza; Azam, Sara; Kumar, Kishore; Niazi, Masooma; Dev, Anil
Abstract : Menetrier's disease (MD) is described as hypertrophied giant gastric folds causing hypoproteinemia due to protein losing gastropathy and is associated with higher risk of gastric adenocarcinoma. We present a case of a 58-year-old male who presented to our clinic with Melena and endoscopic work up showed enlarged gastric folds and erythematous mucosa in the antrum and three nonbleeding angioectasias in the duodenum. Mucosa biopsies were negative for H. pylori infection. He underwent polypectomy which showed fundic gland polyps. After 1½ years, EGD was repeated for abnormal computerized tomography of abdomen which showed enlarged gastric folds and biopsy revealed gastric fundic mucosa with foveolar hyperplasia, dilated fundic glands, and chronic gastritis. Stomach biopsy results were consistent with MD. Our patient had progressive disease in one and half years. It is important to follow patient with large gastric folds regular as they can develop MD over time which has increased risk of gastric adenocarcinoma.